Quality assurance strategy of pharmacy compounded drugs - O. A. Zdoryk (The State Expert Center of the Ministry of Health of Ukraine, 2019)
Formulations and in-pharmacy preparation process of compounded drugs were being created for centuries, and seem to have no concerns regarding the quality, compatibility and stability during storage or usage. Taking in mind modern trends for quality assurance and standardization of drugs, quality of preparation process of compounded drugs can be proved by using of a systematic approach that is based on pharmaceutical quality systems. Variability of preparation conditions, preparation equipment from pharmacy to pharmacy, personal professional skills require the development of defined standards, rules and summarized the strategy of quality assurance of compounded drugs. The aim of this paper was determination of critical factors and development of the design for quality assurance of compounded drugs. The materials of this study were the regulative base of Ukraine, international documents, guidances and own investigations concerning the requirements for the preparation process and quality control of compounded drugs. The methods used were data systematical analysis, bibliosemantic and summary. The achievement of good quality of compounded drugs can be present as a step-by-step process, that cover adherence to necessary preparation procedure and knowledge of peculiarities of drugs, process understanding, identification of risks and its evaluation, minimization and implementation of the quality management system for documentation, equipment and personnel. As a result of preparation schemes analysis, the critical factors were determined and the Fishbone diagram was proposed. The factors contributing to the general strategy of compounded drugs quality assurance, such as prescription analysis, personnel, regulative base, conditions of preparation process and equipment, documentation, dispensing, characteristics of active ingredients and additives, compounding design, preparation technology, containers and package, quality control, stability and labelling were determined. The proposed diagram of causes and effects can be used as a template for the identification and quantification of risks during preparation and quality control of compounded drugs. The proposed general scheme for quality assurance is necessary for organization and optimization of monitoring preparation and quality control, implementation of remedial and preventive measures, tracking of causes, nonconformities, and prevention of its repetition, management of variables, determination of improvement possibilities and audit conducting.